Effort-reward imbalance and video display unit postural risk factors interact in women on the incidence of musculoskeletal symptoms. - Lapointe, Julie; Dionne, Clermont E.; Brisson, Chantal; Montreuil, Sylvie (Work, 2013)
OBJECTIVE: This study investigated gender-specific interaction between effort-reward imbalance and video display unit (VDU) postural risk factors at work on the incidence of self-reported musculoskeletal symptoms in the shoulder-neck, lower back and upper limbs regions. PARTICIPANTS: A cohort of 2,431 VDU users - consisting of white-collar workers in three Canadian public service organizations - was assessed on postural risk factors and effort-reward imbalance at work. METHODS: After a mean follow-up time of three years, the six-month incidence proportion of musculoskeletal symptoms in each body region was measured. Interaction was estimated with the attributable proportion of cases due to interaction. RESULTS: For women, two significant attributable proportions due to interaction between effort-reward imbalance and postural risk factors were observed in the shoulder-neck (64%) and upper limbs (57%) regions, while an interaction of 25%, although not significant, was observed in the lower back. No interaction was observed for men. CONCLUSIONS: This interaction means that, among women, when effort-reward imbalance and postural risk factors are simultaneously present, the incidence of musculoskeletal symptoms is greater than the sum of effects of the individual factors. Successful interventions on either one of these exposures would thus have the supplemental benefit of preventing cases due to interaction.